Effect of high planting densities and cultivars on productivity of rainfed maize (Zea mays) - SINGH, PERMENDRA; KUMAR, ANIL; GUPTA, VIKAS; KUMAR, JAI; SINGH, BRINDER (The Indian Journal of Agricultural Sciences, 2019)
An experiment was conducted at research farm of Advanced Centre of Rainfed Agriculture (ACRA), Rakh Dhiansar SKUAST-Jammu, using factorial randomized block design (FRBD) with three replications to study the effect of planting densities on plant growth and productivity of maize varieties. The experiment consisted of two maize varieties, viz. Double dekalb and Mansar and six plant spacings of 40 × 15, 40 × 20, 50 × 15, 50 × 20, 60 × 15 and 60 cm × 20 cm. Varieties and planting density had a significant effect on plant height, dry matter accumulation, leaf area index (LAI) and yield attributes like cob length, cob girth, number of grain row/cob, number of grains/cob row, number of grains/cob, grain and stover yield. The variety Double dekalb attained significantly higher growth and yield attributing parameter values and grain/stover yield. Spacing of 50 cm × 20 cm observed significantly higher values of grain yield and yield attributing characters. However, 40 cm × 15 cm spacing achieved significantly higher values of plant height, dry matter accumulation, LAI and stover yields. Also the spacing of 50 cm × 20 cm exhibited statistically higher values of N, P and K uptake while 40 cm × 15 cm spacing recorded significantly lowest values of nutrient uptake. Among the varieties Double dekalb exhibited higher values of net returns and B:C ratio values while among the different spacing’s, 50 cm × 20 cm registered the highest net returns and B:C ratio values.